RNA-Sequencing Analyses Demonstrate the Involvement of Canonical Transient Receptor Potential Channels in Rat Tooth Germ Development - Yang, Jun; Cai, Wenping; Lu, Xi; Liu, Shangfeng; Zhao, Shouliang (Frontiers in Physiology, 2017)
Tooth development depends on multiple molecular interactions between the dental epithelium and mesenchyme, which are derived from ectodermal and ectomesenchymal cells, respectively. We report on a systematic RNA sequencing analysis of transcriptional expression levels from the bud to hard tissue formation stages of rat tooth germ development. We found that GNAO1, ENO1, EFNB1, CALM1, SIAH2, ATP6V0A1, KDELR2, GTPBP1, POLR2C, SORT1, and members of the canonical transient receptor potential (TRPC) channel family are involved in tooth germ development. Furthermore, Cell Counting Kit 8 (CCK8) and Transwell migration assays were performed to explore the effects of these differentially expressed genes (DEGs) on the proliferation and migration of dental pulp stem cells. Immunostaining revealed that TRPC channels are expressed at varying levels during odontogenesis. The identified genes represent novel candidates that are likely to be vital for rat tooth germ development. Together, the results provide a valuable resource to elucidate the gene regulatory mechanisms underlying mammalian tooth germ development.